CUSTOMER EXPERIENCE IN E-RETAILING - A STUDY IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
For many years, the retail market has been an attractive industry for industrialists and researchers alike. However, with the rise of technology, a new research area has emerged, focusing on understanding customer experience in the online retail market. In India, a large percentage of internet users use online mode to get product information, compare costs, and read product reviews. However, the inability to physically inspect products before purchase is the biggest barrier to online shopping in India, which can lead to uncertainty in the product quality. Although e-retail in India has skyrocketed above global purchasing rates in several categories, Indian e-retailers are not well-directed, and their shopping experiences are not seamless. Due to a lack of comprehensive research, Indian e-retailers have not incorporated a strong business rationale for customer experience, nor have they effectively integrated different customer experience methods into their marketing tactics. It is crucial to systematically explore how companies can alleviate unfavorable experiences and negative consequences and improve Indian consumer behavior concerning online shopping.